Gambaran Konsumsi Makanan Tradisional pada Balita di Keluarga Pesisir di Kota Bengkulu, Indonesia: Consumption Traditional Food Description in Children Under Five in the Coastal Family of Bengkulu City, Indonesia - Betty Yosephin Simanjuntak; Desri Suryani; Miratul Haya; Ali Khomsan (Universitas Airlangga, 2023)
Background: Traditional food is the most potent food to develop and is an essential component in intervention strategy for increasing toddler daily consumption. Traditional food contributes to micro-nutrition and protein, which are needed for toddler growth. Objectives: This research aimed to identify traditional food and toddlers' traditional food consumption in coastal families in three ethnicity in Bengkulu. Methods: This research used a cross-sectional design. Samples were mothers as food givers in the family, and the analysis unit was the toddler, in a total of 115, picked randomly from 137 households with 12-59 months old toddlers. Data was collected using quantitative and qualitative techniques, in-depth interviews, and food recall forms. Traditional food identification comes from FFQ (Food Frequency Questionnaire). Consumption of toddler fisherman family data that had been collected and compared with RDA 2019. Analyses were done by formulating the results from the in-depth interview and uni variate analysis. Results: Traditional food contribution to fisherman's toddler contained 19.34% energy, 40.86% protein, 17.65% fat, 17.65% carbohydrate, 16,3% PUFA fat acid, and 13.8% MUFA. Many different traditional foods often consumed by Melayu, Serawai, and Minang ethics in coastal families could be classified as fish, vegetables, and snacks. Conclusions: Traditional food contribution could fulfill nutritional needs of energy and macro-nutrients ranging from 17-41%. We must increase traditional food consumption in coastal families by varying processing so that each ethnicity's distinctive taste in traditional food can be maintained.